Storage and Flux of Nutrients in Disturbed and Undisturbed Tropical Moist Forest of Eastern Nepal - Tilak Prasad Gautam; Tej Narayan Mandal (International Journal of Forestry Research)
The disturbance activities in tropical forests shrink the nutrient cycling between the vegetation and soil. To understand the nutrient cycling in undisturbed and disturbed stands of mixed deciduous tropical forest of eastern Nepal, plant biomass was estimated within seventy randomly established sampling plots. The biomass values were multiplied with nutrient concentration of respective parts to estimate the nutrient stocks. The nutrient concentrations varied widely amongst components. In trees, concentrations of all nutrients were highest in leaves followed in decreasing order by fine roots (<5 mm) and twigs and then by branches, bole, and coarse roots. The contribution of different components to total nutrient stocks was in the following order: tree > stand fine root > shrub > herb, in both stands. The relative contribution of different components of trees to total nutrient stocks was in the following order: bole > coarse root > branch > leaf > twig > fine roots. In trees, leaves and fine roots had greater gross uptake of nutrients than other components. The concentrations of different nutrients in the plants are in the following order: nitrogen > potassium > phosphorus. Total nutrient return to the soil through the litterfall is almost 1.5 times greater than that from fine roots in both forests. In conclusion, various types of forest disturbances had adverse effect on the nutrient stocks and nutrient dynamics.